Lingual Foregut Duplication in a Middle-Aged Adult - Patel, P.; Branstetter, B.F.; Myers, E.N. (American Journal of Neuroradiology, 2011)
SUMMARY: Lingual duplication cysts are rare in the pediatric population and exceedingly rare in adults. Imaging is an important part of the evaluation of lingual lesions and is helpful in defining the location and extent for surgical planning. We present a lingual duplication cyst and discuss the imaging findings and radiologic differential diagnosis.